Influence of HIV Infection and Antiretroviral Therapy on Bone Homeostasis - Delpino, María Victoria; Quarleri, Jorge (Frontiers in Endocrinology, 2020)
The human immunodeficiency virus type 1 (HIV)/AIDS pandemic represents the most significant global health challenge in modern history. This infection leads toward an inflammatory state associated with chronic and immune dysregulation activation that tilts the immune-skeletal interface and its deep integration between cell types and cytokines with strong influence on the skeletal renewal and exacerbated bone loss. Hence, reduced bone mineral density is a complication among those HIV–infected individuals that may progress to osteoporosis, thus increasing their prevalence of fractures. The highly active antiretroviral therapy (HAART) can effectively control HIV replication but, the regimens that include tenofovir disoproxil fumarate (TDF) may accelerate bone mass density loss. Molecular mechanisms of HIV-associated bone disease include the OPG/RANKL/RANK system dysregulation. Thereby, the osteoclastogenesis and osteolytic activity are promoted after osteoclast precursor infection, accompanied by a deleterious effect on osteoblast and its precursor cells, with exacerbated senescence of mesenchymal stem cells (MSCs). This review summarizes recent basic research data on HIV pathogenesis and its relation to bone quality. It also sheds light on HAART-related detrimental effects on bone metabolism, providing a better understanding of the molecular mechanisms involved in bone dysfunction and damage as well as how the HIV-associated imbalance on the gut microbiome may contribute to bone disease.